2014
DOI: 10.1186/1471-2164-15-1009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the Hsf family in soybean and functional identification of GmHsf-34 involvement in drought and heat stresses

Abstract: BackgroundHigh temperature affects organism growth and metabolic activity. Heat shock transcription factors (Hsfs) are key regulators in heat shock response in eukaryotes and prokaryotes. Under high temperature conditions, Hsfs activate heat shock proteins (Hsps) by combining with heat stress elements (HSEs) in their promoters, leading to defense of heat stress. Since the first plant Hsf gene was identified in tomato, several plant Hsf family genes have been thoroughly characterized. Although soybean (Glycine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 52 publications
7
89
1
1
Order By: Relevance
“…At least 75 up-regulated heat stress-responsive calmodulin superfamily proteins were expressed in VS16 (Table 9; Supplementary Table S11). In a recent study, the genome-wide transcriptome analysis of soybean identified various Hsfs in drought, low temperature, and ABA stress responses (Li et al 2014). The genotype AP13 exhibited 11 up-regulated Hsfs and also identified two calcium Atpase.…”
Section: Discussionmentioning
confidence: 99%
“…At least 75 up-regulated heat stress-responsive calmodulin superfamily proteins were expressed in VS16 (Table 9; Supplementary Table S11). In a recent study, the genome-wide transcriptome analysis of soybean identified various Hsfs in drought, low temperature, and ABA stress responses (Li et al 2014). The genotype AP13 exhibited 11 up-regulated Hsfs and also identified two calcium Atpase.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 20 non-redundant HSFs were extracted from the initial 22 HSF sequences of chickpea (Table 1), the polypeptide lengths of chickpea HSFs varied significantly from 156 to 500 amino acids. Previously, 25, 22, 21, 38, and 13 HSFs were identified in rice, Arabidopsis, cucumber, soybean and Triticum urartu with polypeptide length ranged from 249-514, 244-495, 184-560, 213-510, and 266-567 amino acids, respectively Zhou et al, 2013;Li et al, 2014;Yang et al, 2014). Isoelectric points (IP) of chickpea HSF proteins were also diverse ranging from 4.42 to 9.25.…”
Section: Identification Of Hsf Proteins From Chickpea Genomementioning
confidence: 97%
“…Hsfs were initially characterized and cloned in yeast ( Saccharomyces cerevisiae ) (Sorger and Pelham, ), followed by various plants (Huang et al ., ; Singh et al ., ; Yabuta, ). With the genome sequencing of more and more plant species, the Hsf gene family has been thoroughly identified and characterized in alfalfa (Friedberg et al ., ), Arabidopsis thaliana (Guo et al ., ), rice ( Oryza sativa L.) (Chauhan et al ., ; Jin et al ., ; Wang et al ., ), maize (Lin et al ., ), Populus trichocarpa and Medicago truncatula (Wang et al ., ), Glycine max (Chung et al ., ), wheat (Chauhan et al ., ), Chinese cabbage (Song et al ., ), pepper ( Capsicum annuum L.) (Guo et al ., ), legume (Lin et al ., ), cotton ( Gossypium hirsutum ) (Wang et al ., ), soybean (Li et al ., ), pear ( Pyrus bretschneideri ) (Qiao et al ., ), Brassica rapa pekinensis (Huang et al ., ), Populus euphratica (Shen et al ., 2015), tea plant ( Camellia sinensis ) (Liu et al ., ), strawberry ( Fragaria vesca ) (Hu Y et al ., ) and wild Chinese grapevine ( Vitis pseudoreticulata ) (Hu et al ., ). So far, plant Hsfs have been found to be widely involved in plant development, heat stress, drought stress, salt stress and the plant disease response (Almoguera et al ., ; Cheng et al ., ; Giesguth et al ., ; Hwang et al ., ; Tanabe et al ., ; Yabuta, ).…”
Section: Introductionmentioning
confidence: 99%